Nanostructured Bioceramic Materials 2020 - Kareiva, Aivaras; Inkrataitė, Greta; Daumantas, Liudas (Vilnius University Proceedings, 2020)
The aim of the conference “Nanostructured Bioceramic Materials” is to overview and share information about the newest achievements concerning bioceramic nanotechnologies with the scientic community. During the conference, scientists from chemistry, physics, technology, medicine and implantology will be able to acquaint themselves with synthesis methods, unique properties and applications of bioceramic nanomaterials in implantology.